A review of technologies and applications on versatile energy storage systems. (September 2021) - Zhang, Ziyu; Ding, Tao; Zhou, Quan; Sun, Yuge; Qu, Ming; Zeng, Ziyu; Ju, Yuntao; Li, Li; Wang, Kang; Chi, Fangde
Abstract: The composition of worldwide energy consumption is undergoing tremendous changes due to the consumption of non-renewable fossil energy and emerging global warming issues. Renewable energy is now the focus of energy development to replace traditional fossil energy. Energy storage system (ESS) is playing a vital role in power system operations for smoothing the intermittency of renewable energy generation and enhancing the system stability. We divide ESS technologies into five categories, mainly covering their development history, performance characteristics, and advanced materials. Biomass storage and gas storage are also discussed, which are not considered in most reviews. After detailed research, the rapid development of each technology in recent years is introduced, and some representative research works are surveyed. We comprehensively summarized the advantages and disadvantages of various ESS technologies and presented several evaluation indicators for quantitative analysis. Hybrid ESS is also considered based on the complex market demand. Then, we investigate the applications of various ESS technologies as short-term, medium-term, and long-term storages in power systems, covering the power generation, transmission and distribution, and end-user. Finally, this paper reviews global developing trends, and identifies critical challenges and promising opportunities. Highlights: Comprehensively review five types of energy storage technologies. Introduce the performance features and advanced materials of diverse energy storages. Investigate the applications of various energy storage technologies.